Errors and oral corrective feedback in University English Classes - Ting, Su Hie; Muriatul Khusmah, Musa; Lu Aileen, Ek-Ling (Universiti Teknologi MARA, 2011)
In a language classroom which focuses on communicative use of English, the matter of whether to correct learners’ errors is often debated. Within this context, the study examined the types of errors which are corrected by instructors. The specific aspects studied were the types of errors made by adult ESL learners in a tertiary institution and the types of corrective feedback used by the instructors. Instructor-student interaction data were obtained from audio recordings of 20 two-hour lessons in an English for Social Purposes course in a Malaysian university. The oral interactions were transcribed and analysed using Lyster and Ranta’s (1997) corrective discourse model. Errors which were not treated with corrective feedback were not included in the study. The three types of errors focused on were phonological, lexical and grammatical. From the data set, 119 incidents of noticed errors were identified. The results revealed a tendency for instructors to notice and respond to grammatical errors, followed by phonological errors but lexical errors did not receive as much attention. The oral corrective feedback was usually given in the form of recasts to reformulate part of the students’ utterance without pointing out the error explicitly. In comparison, the other five types of corrective feedback were less frequent. Sometimes the instructors responded to an error with different kinds of corrective feedback types.